RELIABILITY AND VALIDITY OF VARIOUS FORCE-TIME INDICATORS FOR THE ASSESSMENT OF FINGER AND SHOULDER GIRDLE STRENGTH IN CLIMBING - Michail L. Michailov; Jiří Baláš (Scientific Publishing House. NSA Press, 2023)
The rate of upper limb force development (RFD) is one of the important performance factors in sport climbing. The aim of this study was to investigate the reliability and validity of various force-time indicators for the assessment of finger and shoulder girdle strength in climbing. Ten male lead climbers (climbing ability: advanced; IRCRA: 22 ± 2) performed two RFD and two maximal strength tests for the finger flexor and shoulder girdle muscles (one-arm finger hangs and lock-off s, respectively). The maximal strength tests were used to assess maximal force (Fmax). The RFD tests were used to assess: peak force (Fpeak); time for reaching force representing 25%, 50%, and 75% of the body weight (T25%BW, T50%BW, T75%BW); and absolute and relative RFD indicators (e.g., RFD at 200 ms and 95% Fpeak, respectively). The reliability of the finger flexor RFD indicators was high (intrasession intraclass correlation coefficients - ICC between .760 and .973; intersession ICC between .883 and .955). Intersession reliability of the finger flexor T50%BW and T75%BW reached excellent values (ICC = .949 and ICC = .978, respectively). Reliability of the finger flexor and lock-off Fpeak and Fmax was also high (ICC between .850 and .966). Consistency between Fpeak and Fmax was not satisfactory, though. These variables differed significantly (p = .035) in the finger flexor tests, and ICC was moderate (.605) in the lock-off tests. Most of the lock-off force-time indicators had moderate or poor reliability. Finger flexor and lock-off Fmax/kg and T50%BW correlated significantly (p < .05) with the climbing ability (R = .805, R = .653, and R = -.703, respectively), while lock-off force-time indicators did not. T50%BW was the most reliable and valid force-time indicator in advanced climbers. RFD indicators were reliable, but muscle strength appeared more important than RFD in advanced climbers.